2012
DOI: 10.1371/journal.pone.0044521
|View full text |Cite
|
Sign up to set email alerts
|

Using Networks To Understand Medical Data: The Case of Class III Malocclusions

Abstract: A system of elements that interact or regulate each other can be represented by a mathematical object called a network. While network analysis has been successfully applied to high-throughput biological systems, less has been done regarding their application in more applied fields of medicine; here we show an application based on standard medical diagnostic data. We apply network analysis to Class III malocclusion, one of the most difficult to understand and treat orofacial anomaly. We hypothesize that differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Malocclusion is defined as a misalignment of the teeth or an incorrect occlusion between the upper and lower dental arches [3]. Malocclusion has a significant effect on craniofacial development, oral health and function, as well as the patients’ appearance, and more serious to induce harm to systemic health of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Malocclusion is defined as a misalignment of the teeth or an incorrect occlusion between the upper and lower dental arches [3]. Malocclusion has a significant effect on craniofacial development, oral health and function, as well as the patients’ appearance, and more serious to induce harm to systemic health of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different algorithmic approaches derived from complexity theory showed that malocclusions can be viewed as polytypic structures consisting of a systematic mixture of multiple, competing dentofacial types whose growth trajectories depend on the membership grade of a specific growth strategy [31,32]. How these large-scale, high-dimensional data sets can be integrated to better understand the orthodontic network underlying physiological states associated with malocclusions needs to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…How these large-scale, high-dimensional data sets can be integrated to better understand the orthodontic network underlying physiological states associated with malocclusions needs to be understood. By integrating multiple orthodontic components and regulatory interactions into a comprehensive topological model that goes beyond clinical intuition, emerging mathematical tools such as complex networks and modules' detection could address a variety of biological problems in orthodontics and allow improved interpretation of quantitative patient-specific information [31]. In this study, we applied these promising approaches to the orthodontics with the aim to extract information, infer the craniofacial evolutionary morphogenesis on a topological basis, and obtain a more comprehensive understanding of processes associated with treatment of Class III malocclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Although only one out of four of the examples of the paper were truly power-law networks [5], the mechanism introduced in [4] opened a very prolific era of investigations [6]. Since then, complex networks have become a common language in the interdisciplinary fields [7]; the research has evolved toward several directions, from the most esoteric quantum networks [8], to the more applied field of Network Medicine [9][10][11][12][13], to the recent field of Networks of Networks [14] stimulated by the need of describing interdependent systems [15] -and many more.Nowadays, among the most successful field of application of complex networks are economics and finance; surprisingly, complex networks have revealed much less effective in their original field of birth -social systems.In this issue, we have collected research papers on several topical trends in complex economic, financial and social systems. It is interesting that a consistent fraction of these papers does not need to apply complex networks but resort to much more a…”
mentioning
confidence: 99%
“…Although only one out of four of the examples of the paper were truly power-law networks [5], the mechanism introduced in [4] opened a very prolific era of investigations [6]. Since then, complex networks have become a common language in the interdisciplinary fields [7]; the research has evolved toward several directions, from the most esoteric quantum networks [8], to the more applied field of Network Medicine [9][10][11][12][13], to the recent field of Networks of Networks [14] stimulated by the need of describing interdependent systems [15] -and many more.…”
mentioning
confidence: 99%